Dynamic analysis and simulation of four-axis forced synchronizing banana vibrating screen of variable linear trajectory - Liu, Chu-sheng; Zhang, Shi-min; Zhou, Hai-pei; Li, Jun; Xia, Yun-fei; Peng, Li-ping; Wang, Hong (Journal of Central South University, 2012)
A new concept of banana vibrating screen which has the same effect as traditional banana vibrating screen in a new way was put forward. The dynamic model of vibrating screen was established and its working principle was analyzed when the action line of the exciting force did not act through the centroid of screen box. Moreover, the dynamic differential equations of centroid and screen surface were obtained. The motions of centroid and screen surface were simulated with actual parameters of the design example in Matlab/Simulink. The results show that not only the amplitude has a significant decrease from 9.38 to 4.10 mm, but also the throwing index and vibrating direction angle have a significant decrease from 10.49 to 4.59, and from 58.10° to 33.29°, respectively, along the screen surface, which indicates that motion characteristics of vibrating screen are consistent with those of traditional banana vibrating screen only by means of a single angle of screen surface. What’s more, such banana vibrating screen of variable linear trajectory with greater processing capacity could be obtained by adjusting the relative position of force center and the centroid of screen box properly.